The Existence of Traditional Games Among 5-6 Years Old Children (In RT 23, Kelurahan Kota Baru, Kecamatan Alok Timur, Maumere) - Mbasa, Maria Ernawati N.; Oedjoe, Mintje Ratoe; Betty, Credo; Bunga, Beatriks N. (Asosiasi Pusat Studi Wanita/Gender & Anak Indonesia (ASWGI), 2020)
This research aims to identify the traditional games exist, factors influencing the existence of and describe the attendance at the traditional games in Maumere. This research took place in RT 23, Kelurahan Kota Baru, Kecamatan Alok Timur, Maumere. The subjects of this research were 5-6 years old children, their parents and some officials of RT 23. The data was collected through observation, interviews, and documentation during the research. The results indicated that segong (hopscotch), inggo (hide and seek), ban (rolling wheel) and tali merdeka (jump rope) and several seasonal games still existed as children played the games every day. The presence of people who could teach children the traditional games, the no replacement of modern games, the safety aspects of the game from parents’ perspective and the strong family-tied social life contributed to the survival of traditional games. On the other hand, the decreasing availability of land to play contributed to the extinction of traditional games among children in Maumere.